تعليم اللغة العربية للناطقين بغيرها بين الأغراض الخاصة وأغراض الحياة: مقاربة نظرية وتطبيقية وآفاق مستقبلية/Teaching the Arabic Language for Non-native speakers in between Special and General Life purposes: A theoretical and applied approaches, and future - Abduh Obeidt, Rijan; A. Al-Qudah, Mohammed, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: يهدف هذا البحث إلى إجراء مقارنة تفصيليّة بين تعليم اللغة العربية للناطقين بلغات أخرى، للأغراض الخاصة، وتعليمها لأغراض الحياة (الأغراض العامة)، مع إجراء دراسة ميدانية على عينة من متعلمي العربية من غير الناطقين بها، في مركز اللغات في جامعة اليرموك للوقوف عند مدى قدرة الطلبة على تحديد الغرض من تعلّمهم للغة العربية، وتحديد حاجاتهم لها. وقد اُعتمد في البحث على المنهج الوصفي التحليلي المستند إلى دراسة تطبيقية تعتمد على استبانة محدَّدة الأسئلة. وكان من أبرز النتائج التي توصّل إليها البحث: غياب الاستراتيجية العربية الموحَّدة على غرار الاستراتيجية الأوروبية في تعليم اللغات الحية (ومنها العربية)، وغلبة الرؤى الفردية التي يقدّمها دارسون مختصون، أو مراكز بحثية صغيرة، فيما يتعلق بالجانب النظري والتطبيقي على صعيد بناء البرامج، وغياب الجهود الجماعيّة المتكاملة التي تراكم الخبرات وتستفيد منها، والقصور الواضح في الدراسات التطبيقية التي تقدّم برامج لتعليم العربية لأغراض خاصة، والتداخل بين المفهومات الاصطلاحية، ولاسيّما العربية للحياة والعربية لأغراض خاصة، وغلبة الطابع الاجتهادي لبرامج العربية لكافة برامج تعليم العربية لغير الناطقين بها، نتيجة غياب الاستراتيجية العربية الموحدة. الكلمات المفتاحية: الناطقين بلغات أخرى-العربية للحياة-العربية لأغراض خاصّة-الفروق. Abstract The study aims at conducting a detailed comparison between the teaching of Arabic language for non-native speakers for special and general purposes. A field study was conducted on a sample of non-native Arabic language learners at the Languages Center at Yarmouk university to identify the learners’ ability to determine their purpose and need of studying the Arabic language. The descriptive analytical methods were used in the applied part of the study through a limited number of questionnaires. The most salient conclusions of the study are: lack of unified Arab strategy similar to European strategy for teaching live languages (including Arabic); dominance of individual visions, provided by specialized scholars or small research centres, concerning theoretical and applied aspects on creating programs as well as the lack of integrated and collective efforts that accumulate experiences to benefit from them; the clear shortage in applied studies that offer programs for teaching Arabic, for special purposes; overlapping between concept to understand teaching Arabic for life and Arabic for special purposes; dominance of ad hoc approach in Arabic language for all Arabic language teaching programs for foreigners, as a result of the lack of unified Arab strategy. Keywords: teaching Arabic language, non-native speakers, special purposes, life purposes. Abstrak Kajian ini bertujuan membandingkan di antara mengajar bahasa Arab kepada bukan penutur asli untuk tujuan umum dan khusus. Satu kajian lapangan telah dijalankan terhadap pelajar-pelajar bukan Arab di Pusat Bahasa Universiti Yarmouk untuk mengenalpasti kebolehan mereka untuk menentukan tujuan dan keperluan mempelajari bahasa Arab. Metod deskriptif dan analitikal digunakan untuk bahagian practical kajian melalui agihan soal selidik. Di antara dapatan terpenting kajian ialah: kekurangan strategi bersama Arab yang serupa dengan strategi negara Eropah untuk mengajar bahasa hidup (termasuk bahasa Arab) ; penguasaan visi individu yang diberikan oleh pakar atau pusat-pusat kajian yang kecil berkenaan aspek-aspek teori dan praktikal dalam membuat program juga kekurangan kerjasama untuk memanfaatkan pengalaman masing-masing sebaik mungkin; kekurangan yang jelas dalam kajian gunaan yang menawarkan kursus-kursus dalam pengajaran Bahasa Arab untuk tujuan khas; pertindihan di antara konsep untuk memahami pengajaran bahasa Arab untuk tujuan kehidupan dan khas; banyaknya pendekatan tidak terancang dalam program pengajaran Bahasa Arab kepada bukan Arab kerana ketiadaan inisiatif strategik untuk mengisi jurang tersebut. Kata kunci: Pengajaran Bahasa Arab – bukan penutur Arab asal – tujuan khas – tujuan kehidupan